Effect of one Laptop per Child Policy on academic Performance in Social Studies in Ruhango District, Rwanda. - Jean, Libanje Pierre (Kabale University, 2020)
The project “One Laptop per Child” has been implemented in Rwanda since 2008 to bridge the digital divide between urban and rural and remote communities and also provide solution to the challenges facing Rwanda’s education in addition to improvement in academic performance. The purpose of the study was to evaluate the effect of one laptop per child policy on academic performance in social studies in Ruhango District so as to propose necessary strategies to improve teaching-learning social Studies. The specific objectives were to examine whether the children who used One Laptop per Child in P4-p5 perform better in their Social Studies than those who did not; to investigate challenges faced by teachers in Ruhango primary schools in teaching Social Studies and to suggest solutions and recommendations to the challenges. A survey study was done. The study population was 3,984 and Krejcie & Morgan’s table for determining sample size was used to get the sample size of 351 respondents. Therefore the study was mainly based on data from 351 respondents including 36 teachers of social Studies; 288 P4 and P5 pupils from both Schools using and not using OLPC Laptops; 18 head teachers from both schools using and not using OLPC laptops and 9 Sector Education Officers (SEOs).The researcher adopted both qualitative and quantitative methods of data collection through self- administrated questionnaire, interview guide, interpretations of the results in Social Studies and library search. The findings revealed that in general, schools with OLPC laptops perform better than schools without OLPC laptops. This was because teachers using OLPC in class had access to a greater range of resources to use with their pupils as well as diversify their lessons using the laptops. Among the challenges facing teachers was the time per week allocated to the course which is not enough for pupils in primary schools to cover the content and carry further Research to improve their knowledge in the subject. It was also found out that parents do not assist their children in learning and revising their lessons at home. One major recommendation was that the Ministry of Education should motivate the teachers by improving their lifestyle so that they should fully use their time in improving the teaching-learning process through updated materials and new teaching methods, including the integration of OLPC based learning as this requires extra time.